The essential Davidson - Davidson, Donald, 1917-2003 (Clarendon Press : Oxford University Press, 2006)
The Essential Davidson compiles the most celebrated papers of one of the twentieth century's greatest philosophers. With a new introduction by Ernie Lepore and Kirk Ludwig, two of the world's leading authorities on his work, the volume distils Donald Davidson's seminal contributions to our understanding of language, the mind, action, and knowledge, spread over three decades' worth of essays, into one thematically organized collection. It will be invaluable for anyone. seeking a single reference point for some of the most brilliant and influential academic writing of recent times. - ;The Essent.